The Use of Reported Past Tense in Gossip Narratives: A Study on Turkish Textbooks for Foreigners - Öztürk, Burcu; Tekin, Nazik Müge (Australian International Academic Centre, 2022)
The reported past tense is one of the basic grammar topics taught to learners in the teaching of Turkish as a foreign language. It is explained in the Turkish textbooks used for foreign language teaching that this mode has functions of “hearing from another” and “become aware of the events in a later time”. In our daily lives, this mode is not welcomed well to a certain extent in society; however, it is also used in “gossip” in relation to the function of hearing from someone else. Although gossip narratives in Turkish textbooks for foreigners are included as one of the examples of this mode, it is not explained for what purpose this mode serves. In this study, the functions of the reported past tense with “-mIş” morpheme in Turkish were summarized based on the relevant literature and with reference to the literature with the usage of verbs conjugated with “-mIş” suffix in gossip narratives were emphasized; by focusing on how “-mIş” suffix is presented in the textbooks for teaching Turkish to foreigners, the inclusion of gossip-functioned texts in the books were evaluated in a critical approach.
Keywords: 4. Education